KUALITAS PELAYANAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA SIAK KOTA PEKANBARU - Gusyandri "; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tirta Siak Regional Drinking Water Company (PDAM) of Pekanbaru City as one of the government agencies in the form of Regionally-Owned Enterprises (BUMD) which has a type of service included in the service group of goods namely services included in the service group of goods namely services that produce as forms / types goods, in this case is the supply of clean water. The purpose of this research is to find out how the quality of service of Tirta Siak Regional Water Supply Company (PDAM) of Pekanbaru City and the factors that inhibit it. The theory used is Zeithaml's theory that there are five dimensions to measure service quality: Tangible, Reliability, Responsiviness, Assurance, and Empathy. This study uses qualitative research with a phenomenological approach and the data needed both primary and secondary data obtained through interview, observation and documentation techniques for subsequent analysis. The results of this study indicate that: first, the service quality of Tirta Siak Regional Water Supply Company (PDAM) of Pekanbaru City is still not fully optimal due to the discovery of several things that are not in accordance with quality service, only one indicator, namely Empathy which has been running properly because it can we see PDAM Tirta Siak has been maximized in terms of giving good empathy to its customers. While Tangible indicators, Reliability, Responsiveness, Assurance which can be concluded have not been implemented properly, because there are still conflicts with the Perda, vision and mission, and good SOPs. the factors that hinder the Quality of Service Tirta Siak Regional Drinking Water Company (PDAM) Tirta Siak Pekanbaru City, namely: Facilities and Infrastructure and human resources.                                                                                                                          Keywords: Public Service ,Quality of Service, Good Governance.